Global output feedback stabilisation of a class of stochastic systems with unknown growth rate. Issue 4 (3rd April 2021) - Li, Hanfeng; Zhang, Xianfu; Wang, Zi-Ming; Wei, Airong
ABSTRACT: This paper is concerned with the global output feedback stabilisation problem for a class of stochastic systems with unknown growth rate. The output of the system under consideration contains unknown measurement sensitivity, and the nonlinear terms of the system are assumed to be bounded by states multiplied by an unknown constant. An improved double-domination approach, in which one time-varying gain dominates the unknown nonlinear terms and another constant gain dominates unknown measurement sensitivity, is successfully proposed to construct a full-dimensional state observer and an output feedback controller. Further, it is shown that all signals of the resulting closed-loop system converge to zero almost surely. The effectiveness of the proposed control scheme is demonstrated by a simulation example.